The Effect of Dialogue and Debate Strategy in the Development of speaking skills of the Jordanian fourth Grade students in North eastern Badia Directorate of Education - ALazamate, Hael (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This study aimed at investigating the effect of dialogue and debate strategy in the Development of speaking skills of the Jordanian fourth Grade students in North eastern Badia Directorate of Education. This study used the qusai - experimental design along with the descriptive method in term of using pre_ post tests and a questionnaire Male and female teachers. The sample of the study consisted of (108) Jordanian fourth grade students and (68) male and female Arabic language teachers who teach the fourth grade in north eastern Badia directorate of education in the academic year 2017_2018. to achieve the purpose of study the researcher distributed the sample of the study into tow experimental groups and two control groups. to achieve the purpose of the study descriptive statistics and MONCOVA were used. The results of the study showed that the experimental groups out performance and it was in favor of females also.